Exploratory Use of Decision Tree Analysis in Classification of Outcome in Hypoxic–Ischemic Brain Injury - Phan, Thanh G.; Chen, Jian; Singhal, Shaloo; Ma, Henry; Clissold, Benjamin B.; Ly, John; Beare, Richard (Frontiers in Neurology, 2018)
Background: Prognostication following hypoxic ischemic encephalopathy (brain injury) is important for clinical management. The aim of this exploratory study is to use a decision tree model to find clinical and MRI associates of severe disability and death in this condition. We evaluate clinical model and then the added value of MRI data. Method: The inclusion criteria were: age ≥17 years, cardio-respiratory arrest and coma on admission (2003-2011). Decision tree analysis was used to find clinical (Glasgow Coma Score/GCS, features about cardiac arrest, therapeutic hypothermia, age, sex) and MRI (infarct volume) associates of severe disability and death. We used the area under the ROC (auROC) to determine accuracy of model. There were 41 (63.7% males) patients having MRI imaging with the average age 51.5 ± 18.9 years old. The decision trees showed that infarct volume and age were important factors for discrimination between mild to moderate disability and severe disability and death at day 0 and day 2. The auROC for this model was 0.94 (95% CI 0.82-1.00). At day 7, GCS value was the only predictor; the auROC was 0.96 (95% CI 0.86-1.00). Conclusion: Our findings provide proof of concept for further exploration of the role of MR imaging and decision tree analysis in the early prognostication of hypoxic ischemic brain injury.